2012
DOI: 10.1021/nl204334x
|View full text |Cite
|
Sign up to set email alerts
|

PMN-PT Nanowires with a Very High Piezoelectric Constant

Abstract: A profound way to increase the output voltage (or power) of the piezoelectric nanogenerators is to utilize a material with higher piezoelectric constants. Here we report the synthesis of novel piezoelectric 0.72Pb(Mg(1/3)Nb(2/3))O(3)-0.28PbTiO(3) (PMN-PT) nanowires using a hydrothermal process. The unpoled single-crystal PMN-PT nanowires show a piezoelectric constant (d(33)) up to 381 pm/V, with an average value of 373 ± 5 pm/V. This is about 15 times higher than the maximum reported value of 1-D ZnO nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 15 publications
1
60
1
Order By: Relevance
“…Yet, high performance devices have to be realized for their potential practical application. Xu et al 24 synthesized PMN-PT NWs via a hydrothermal reaction at low temperature and studied their piezoelectric property (d 33 $ 381 pm V À1 ). Further, they demonstrated the energy generation from exible nanocomposite based nanogenerator consisting of hydrothermally grown PMN-PT NWs -polymeric matrix.…”
Section: -13mentioning
confidence: 99%
“…Yet, high performance devices have to be realized for their potential practical application. Xu et al 24 synthesized PMN-PT NWs via a hydrothermal reaction at low temperature and studied their piezoelectric property (d 33 $ 381 pm V À1 ). Further, they demonstrated the energy generation from exible nanocomposite based nanogenerator consisting of hydrothermally grown PMN-PT NWs -polymeric matrix.…”
Section: -13mentioning
confidence: 99%
“…For example, up to four-inch diameter PMN-PT crystals are now grown routinely with the [001] seeding. More recently progresses have been made in the fabrication of PMN-PT nanowires and nanowire-based nanocomposite [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, rGO formed an electrical bridge between the nanowires and varied the dielectric constant of the device via Maxwell-Wagner-Sillars (MWS) polarization and microcapacitance effects [38]. The generated open-circuit voltage of the device can be calculated as follows [19]:…”
Section: Resultsmentioning
confidence: 99%
“…These studies shown such energy sources to successfully power liquid crystal displays (LCDs), light-emitting diodes (LEDs), implantable biosensors, and many portable personal electronic devices [10]. Various nanostructured materials, such as ZnO [11][12][13], GaN [14], lead zirconium titanate (PZT) [15,16], BaTiO 3 (BTO) [17], NaNbO 3 [18], (1-x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PMN-PT) [19], ZnSnO 3 [20], polyvinylidene fluoride (PVDF) [9], and polytetrafluoroethylene (PTFE) [21] have been widely used for nanogenerator fabrication in a variety of forms, such as micro/nanowires, nanobelts and particles. Among them, ZnO is lead-free, biocompatible and has piezo and semiconducting properties [22,23]; its noncentrosymmetric nature has proven to be advantageous for nanogenerator applications.…”
Section: Introductionmentioning
confidence: 99%